MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN SOAL ULANGAN MELALUI IHT DI SD NEGERI KEMBANGMALANG PADA TAHUN 2021/2022 - Sri Suharyanti; Rahmat Mulyono (STKIP Subang, 2022)
Study Action School this aim knowing is IHT could increase competence teacher in arrange question test in elementary Country Kembangmalang Kapanewon climbing . Implementation IHT on 8 teachers with details 6 teachers class and 2 teachers eye lesson.Study action school this use model cycle PTK Ridwan Abdullah et al . Draft study Kemmis & Mc Tags in do in elementary Country Kembangmalang Kapanewon climbing with amount teacher class and eye lesson as much 8 people, whereas implementation study action this consists from two cycle with method Descriptive quantitative.Results Study show exists enhancement competence teacher in arrange question test daily and in-house training effective . Thing this could seen from results implementation IHT 71.67% Becomes 86,67% , for nara source 72.22% Becomes 88.89%, for participant 69.2% Becomes 85.7%, for sarpras 66% Becomes 87.5% and for results / product question 70% Becomes 88.89% as taking data qualitative . And in results product the more increase as taking data quantitative . Enhancement competence teacher through IHT use also supported seriousness trainers for accompany and push participant , seriousness participant and diligent train , means which complement